Компьютерный жаргон в процессе обучения иностранных студеннтов русскому языку как языку специальности - Заборовская, Светлана (Studia Rossica Posnaniensia, 2015)
This article raises the question of the reasonableness of introducing the basics of computer jargon when teaching specialist language courses for foreign students of preparatory faculties (technical language).